e-Invoice and its impact to SMEs in Malaysia / Muhammad Zulhusni Asri Roslan, Saflina Azis and Mustafa Kamal Mat - Roslan, Muhammad Zulhusni Asri; Azis, Saflina; Mat, Mustafa Kamal (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Electronic invoicing is also known as e-invoicing, is the digital exchange of invoice data between a supplier and a buyer in a structured format. It involves the automated creation, transmission, receipt, processing, and archiving of invoices using specialized software or services. Small and medium-sized enterprises (SMEs) are facing challenges in adhering to e-invoice regulations, mainly because of the substantial upfront expenses associated with implementing new software and the technical know-how needed for this process. This could make them less competitive and slow down their progress in the digital economy by putting a strain on their finances and disrupting their operations.